Structural Health Monitoring del Patrimonio storico-artistico La Sala dei Battuti del Duomo di Conegliano - Casarin, Filippo; Beccaro, Emma; Fattoretto, Matteo; Girardello, Paolo (Archeomatica, 2013)
Il monitoraggio strutturale è una pratica sempre più applicata nell'ottica della conservazione e dello studio dei beni culturali. In questo lavoro viene presentato l'utilizzo di una nuova metodologia contactless di controllo delle lesioni strutturali adatta all'applicazione in contesti di superfi ci di particolare pregio: nel caso specifi co il ciclo di affreschi della splendida Sala dei Battuti del Duomo di Conegliano. Structural health monitoring (SHM) is increasingly being considered in the field of conservation of cultural heritage buildings, as an activity of primary importance in the definition of the actual structural response of historical buildings or monuments, allowing to express judgments about their health conditions, e.g. worsening or stability of the observed damage pattern...). The paper shows the results obtained by the Structural Health Monitoring system installed in the Hall of Flagellants in the Conegliano Cathedral (TV), which presents a serious crack pattern. The system, which develops an innovative contactless technology relying on an optical video camera, designed in order to avoid any damage to the frescoed surface, has ensured and continues to ensure an effective control of the structure, validating the proposed technology.